Characteristic trace fossils from Miocene brackish-water deposits in the Niger Delta, Nigeria - Ezeh, Sunny C.; Mode, Wilfred A.; Ozumba, Berti M. (Geologos, 2018)
Miocene deposits in the eastern portion of the Greater Ughelli, Central Swamp and Coastal Swamp depobelts contain well-developed brackish-water trace fossil assemblages. Twelve ichnogenera have been identified, namely: Asterosoma, Bergaueria, Chondrites, Gyrolithes, Thalassinoides, Lockeia, Palaeophycus, ?Conichnus, Planolites, Siphonichnus, Skolithos and Diplocraterion. In addition, common non-descript, passively filled burrows and fugichnia (escape structures) have also been observed. The above-mentioned ichnogenera and associated non-descript structures can be arranged into six distinct and recurring ichnoassociations within the Greater Ughelli, Central Swamp and Coastal Swamp depobelts. Each ichnoassociation is comprised of a group of trace fossils which collectively reflect specific environmental conditions during deposition of these Miocene strata. All trace fossil assemblages illustrate deposition in nearshore, restricted settings. Ichnological and sedimentological criteria which may be utilized to recognise brackish-water deposits are discussed and illustrated in pictures of the cores studied.